2018
DOI: 10.12688/f1000research.15373.1
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital cardiac arrest resuscitation performed by the hospital emergency team: A 6-year retrospective register analysis at Danderyd University Hospital, Sweden

Abstract: Background: Cardiac arrest requires rapid and effective handling. Huge efforts have been implemented to improve resuscitation of sudden cardiac arrest patients. Guidelines around the various parts of effective management, the chain of survival, are available. The aim of the present retrospective study was to study sudden in-hospital cardiac arrest (IHCA) and the outcomes of emergence team resuscitation in a university hospital in Sweden. Methods: The Swedish Cardiopulmonary Resuscitation Registry was used to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 9 publications
0
10
1
3
Order By: Relevance
“…Although the ROSC and 24-hour survival rates in our study (70% and 50%, respectively) were higher than those reported by another study conducted in Turkey 13 years ago (49.3% and 28.5%, respectively), the discharge survival rate was lower in our study (9.7% vs. 13.4%) 4. However, discharge survival rates range between 0% and 42% in the literature, and large-scale studies have reported rates of approximately 20% 7,8,21. We think that a higher proportion of patients over the age of 65 years, CCI scores of ≥6 associated with underlying chronic diseases, and CPR durations of >20 minutes might be important factors contributing to the lower discharge and long-term survival rates in our study.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Although the ROSC and 24-hour survival rates in our study (70% and 50%, respectively) were higher than those reported by another study conducted in Turkey 13 years ago (49.3% and 28.5%, respectively), the discharge survival rate was lower in our study (9.7% vs. 13.4%) 4. However, discharge survival rates range between 0% and 42% in the literature, and large-scale studies have reported rates of approximately 20% 7,8,21. We think that a higher proportion of patients over the age of 65 years, CCI scores of ≥6 associated with underlying chronic diseases, and CPR durations of >20 minutes might be important factors contributing to the lower discharge and long-term survival rates in our study.…”
Section: Discussioncontrasting
confidence: 78%
“…Despite significant improvements in the field of cardiopulmonary resuscitation (CPR) over the past 40 years, disparate results have been reported in the literature on survival rates after in-hospital cardiac arrest (IHCA) 16. In addition to immediate CPR by trained personnel, the primary or comorbid diseases of the patient are important in long-term survival after IHCA 7,8…”
mentioning
confidence: 99%
“…Thus, it is not surprising that reports on ROSC and survival to hospital discharge or 30-day survival vary considerably. 9,115À118,134À137 The chance of ROSC varies from 36% 117 to 54% 135 and the chance of survival to discharge/30 days varies from 15% 117 to 34%. 135…”
Section: Ihca Outcomementioning
confidence: 99%
“…The ROSC rate ranges from 35.7% to 54.0% in different patient cohorts. [ 2 3 5 11 12 13 ] We found that coexisting comorbidities, including CKD and COPD, were the independent risk factors related to ROSC. A previous study revealed that patients who did not have comorbidities included in CCI have a higher survival rate.…”
Section: Discussionmentioning
confidence: 94%